Interpretable fuzzy-embedded deep neural network with its application in stock trading - Koh, Amadeus Ying Jie (Nanyang Technological University, 2023)
Neural networks have become increasingly common over the years, being used in a wide range of applications. They are machine learning models designed to simulate the structure and function of the human brain, consisting of neurons which process and transmit information. Neural networks have the capability of recognizing patterns in data and learning complex functions, and therefore are able to form accurate predictions, commonly in regression or classification problems. They are undoubtedly a powerful tool and bring great value to many industries.